Inherent Agency Conflict Built Into The Auditor Remuneration Model - Morawska, Sylwia; Staszkiewicz, Piotr (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper provides a model for audit market interventions. The study asks whether interventions in the audit market result in excessive premiums at the cost of quality and independence. The model was tested based on a historical data sample of 1,927 companies’ fiscal year financial statements, observed for the period 2010–2013. The testing strategy combined statistical analysis of the market concentration and regression of abnormal results. The findings do not support, for the Polish market, the conclusion that the audit market is used as a leverage for consulting services. This paper discusses possibilities of systematic risk for policymakers as a result of the negative interaction between regulated and non-regulated markets.